VD_FINDINFO Jug / 2019 / 54 vom 26. Juni 2017 - VD Tribunal cantonal (2017)
TRIBUNAL FÉDÉRAL, FRAIS DE LA PROCÉDURE, INDEMNITÉ ÉQUITABLE, DÉCISION DE RENVOI, DÉPENS | 41 CO, 406 al. 1 let. a CPP (CH), 433 al. 1 CPP(CH), 433 CPP (CH)